VISUAL RE-BRANDING IDENTITY SEBAGAI STRATEGI PROMOSI MUSEUM TEKSTIL - Arief Yulianto (LPPM Universitas Bina Bangsa, 2023)
The Textile Museum is a museum established in 1976 which was pioneered by Mr. Ali Sadikin as the governor of DKI Jakarta at that time. This museum stands in a cultural heritage building and is currently managed by the DKI Jakarta Provincial Government, the problem that is felt at this time is the lack of promotional media made due to limited human resources, besides that after Covid visitors who come are also starting to gradually decrease. Therefore, one of the efforts of the Community Service team (PKM) from Universitas Media Nusantara Citra held a visual socialization of identity re-branding. The purpose of this activity is as a promotional strategy to help direct branding and introduce the Textile Museum more widely. This activity method begins with the stages of conducting initial concepts, interviews, research, brainstorming, final concepts and design design. The result of this Community Service activity is a visual identity design that can be used by the Textile Museum to promote. In addition, this activity generates understanding and literacy to Textile Museum partners on the importance of visual identity in a brand to develop Textile Museum branding in the future. Where, the existence of this visual identity can be implemented optimally, so that the introduction of science offered by the Textile Museum can be known more widely